PENGARUH KEMASAN, HARGA, DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN MIXUE: (Studi Pada Mahasiswa STIE Widya Wiwaha Yogyakarta) (Prosiding dan Call Paper Widya Wiwaha, 2023)
The purpose of this study is to test whether packaging, price, and product quality affect the purchase intention of Mixue consumers. The data analysis technique uses multiple linear regression using the SPSS (Statistical Program for Social Science) program. The sample studied was 40 people. The technique used in sampling is purposive sampling technique. The findings of this study are as follows: First, packaging has no positive and significant effect on the purchase intention of Mixue consumers. Second, price has no positive and significant effect on Mixue consumer buying interest. Third, product quality has a positive and significant impact on Mixue consumer buying interest. Fifth, packaging, price, and product quality simultaneously have a significant effect on Mixue consumer buying interest. The implication of this research, if the packaging, price, and product quality are good, it will increase consumer buying interest.
Keywords: Packaging; Price; Product Quality; Purchase Intention